Sudden floating thrombus formation on the delivery cable before Amplatzer‐Amulet device deployment during left atrial appendage occlusion: The need for a standardized anticoagulation. Issue 3 (14th June 2019) - Talanas, Giuseppe; Sanna, Giuseppe D.; Portoghese, Michele; Parodi, Guido
Abstract: Anticoagulation is of paramount importance during left atrial appendage occlusion procedure (LAAOP) to prevent periprocedural stroke. We present the case of a 66‐year‐old male patient who was scheduled to undergo LAAOP because of a prior intracranial bleeding. After transesophageal echocardiography‐guided transseptal puncture, intravenous heparin 5, 000 IUs were administered obtaining an ACT greater than 300 s. We planned to implant an Amplatzer‐Amulet 25 mm LAA occluder through the dedicated 12F delivery sheath. After starting the tug test, TEE suddenly showed a floating thrombus whose proximal part was connected to the delivery cable. Because transesophageal echocardiography showed a good position of the device, we decided to release it and to quickly retrieve as a unit into the right atrium both the delivery cable with attached thrombus and the delivery sheath. We discuss about periprocedural anticoagulation dosing and monitoring and the importance to have specific studies in the setting of LAAOP.